Larger, counter-intuitive and lasting – The PSM role in responding to the COVID-19 pandemic, exploring opportunities for theoretical and actionable advances. Issue 3 (June 2021) - van Hoek, Remko
Abstract: PSM has played an important role in the initial mitigation of risks caused by the COVID-19 pandemic. We explore the nature and scope of this role and develop a roadmap for PSM contributions towards greater supply chain resilience. We find that the role of PSM is (1) multidimensional; responding to supply risks but also to demand and logistics risks, (2) counter to game theory; collaboration increased instead of decrease, (3) multi-stage; beyond the initial response the hardest change efforts are still ahead. The pandemic is accelerating the journey towards future-proof PSM but not necessarily revolutionizing the future of PSM. Highlights: PSM has played an important role in the initial mitigation of risks caused by the COVID-19 pandemic. We develop a roadmap for PSM contributions towards greater supply chain resilience. The role of PSM is multidimensional, counter to game theory, multi-stage.